Statistical yearbook - United Nations Educational, Scientific and Cultural Organization; United Nations Educational, Scientific and Cultural Organization (England Unesco, 1980)
"Reference tables, education, science and technology, and culture and communication."
Text in English and French.
Keywords: Intellectual life -- Statistics; Literacy -- Statistics